2017
DOI: 10.32674/jis.v7i2.386
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Institutions and International Students’ Hindrances: A Case of Students From the African Portuguese-Speaking Countries at Two European Portuguese Universities

Abstract: We present a study to comprehend if the support given by higher education institution (HEI) to international students coming from the PortugueseSpeaking African Countries meets their academic and social hindrances. Our starting point was a set of semi-structured interviews focused on the perspectives of these students, their Professors and Course Directors as well as on the perspectives of HEI’ staff. Despite findings indicate a positive institutional support, it seems there is still much to do in order to do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…. Identical experiences have also been reported in previous studies conducted with international doctoral students (Archer 2008;Gardner 2008a;Sherry et al 2010), and with those coming from Portuguese-speaking African countries (Ambrósio et al 2017;Lopes and Diogo 2019). These studies suggest that students who do not fit the traditional mold of graduate education in the West (i.e., anyone other than young, white males) struggle to fit into academia, experiencing negative interactions with others and a general feeling of 'differentness'.…”
Section: Networkingsupporting
confidence: 67%
“…. Identical experiences have also been reported in previous studies conducted with international doctoral students (Archer 2008;Gardner 2008a;Sherry et al 2010), and with those coming from Portuguese-speaking African countries (Ambrósio et al 2017;Lopes and Diogo 2019). These studies suggest that students who do not fit the traditional mold of graduate education in the West (i.e., anyone other than young, white males) struggle to fit into academia, experiencing negative interactions with others and a general feeling of 'differentness'.…”
Section: Networkingsupporting
confidence: 67%
“…From a positive point of view, we could argue that their experience of moving to Portugal and integrating into Portuguese society was 'easier' due to shared language and some level of cultural familiarity, to the extent that host institutions tended to overlook their needs as international students (Ambrósio et al, 2017; see also Sin et al, 2019; see also Santos, 2020;Neto, 2021). Being more circumspect, we also observed that students from the former Portuguese African colonies were highly dependent on programmes created by the government of Portugal or home country administrations, with systematic problems reported about the late payment of scholarships, with waits of up to four months after the start of exchanges, and grants being pegged at levels insufficient to cover basic living cost (see also Ambrósio et al, 2017;Doutor & Alves, 2020). In fact, as we shall discuss, most of the costs of their education tended to be covered by parents or students through working in informal jobs (see also Jardim, 2013).…”
Section: Educational Choices In the Post-colonial Student Worldmentioning
confidence: 99%
“…As students’ vulnerability becomes increasingly apparent during overseas placement, there should be a greater emphasis placed upon the need for HEIs, both home and host institutions, to expand their scope of support by providing adequate security and protection to students (Yang, 2019). This argument is echoing the crescendo of calls for HEIs to understand better and act upon their responsibility towards both outgoing and incoming international students (Ambrósio et al, 2019; Lapina et al, 2016). As university leaders have always been perceived as traditional role models on ethics that substantially engage and can influence other agencies and organisations (Keohane, 2006; Lozano et al, 2013; Prisacariu and Shah, 2016), HEIs should therefore render the protection that is required by their mobile students.…”
Section: Ethical Implications Of Student Mobilities and What Our Study Has Highlightedmentioning
confidence: 99%